2022
DOI: 10.1039/d1an02327f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid separation of cannabinoid isomer sets using differential mobility spectrometry and mass spectrometry

Abstract: With legalization and decriminalization of cannabis in many parts of the world comes the need for rapid separation and quantitation of the psychoactive ingredients. Here, we demonstrate the use of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 52 publications
0
13
1
Order By: Relevance
“…Linear response of each argentinated cannabinoid was not impacted by matrix components or high concentrations of CBC and CBD, as shown by the calibration curves in Figure S15 ( R 2 > 0.99). Moreover, LODs and LOQs associated with the argentination approach are comparable to those associated with DMS-based quantitation of cannabinoids as anions in an IPA-modified environment (LOD ∼ 20 ppb; see Tables S4 and S7 in ref ). Multiplication of the X-intercept determined from linear regression by the dilution factor yields concentrations of Δ 8 /Δ 9 -THC that align with those stated by the manufacturer (Table ).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Linear response of each argentinated cannabinoid was not impacted by matrix components or high concentrations of CBC and CBD, as shown by the calibration curves in Figure S15 ( R 2 > 0.99). Moreover, LODs and LOQs associated with the argentination approach are comparable to those associated with DMS-based quantitation of cannabinoids as anions in an IPA-modified environment (LOD ∼ 20 ppb; see Tables S4 and S7 in ref ). Multiplication of the X-intercept determined from linear regression by the dilution factor yields concentrations of Δ 8 /Δ 9 -THC that align with those stated by the manufacturer (Table ).…”
Section: Resultsmentioning
confidence: 76%
“…The separation power afforded by DMS can be enhanced by doping the DMS carrier gas with solvent vapor. The increase in separation power is a consequence of microsolvation, which increases the difference between the ion’s high and low-field mobility and is usually ion-specific. This phenomenon is rooted in the heating/cooling cycles associated with the field-induced temperature imparted by the SV, where the oscillating waveform drives analyte solvation/desolvation cycles as the ion transitions between the low-field to the high-field portion of the duty cycle. Mashmoushi et al showed that optimal sensitivity and resolution was afforded by detecting the cannabinoids as deprotonated anions in a N 2 DMS environment that is seeded with 1.5 mol % of IPA . However, our attempts to add Δ 8 -THC to this workflow resulted in its coelution with CBD using various chemical modifiers (Figures S2 and S3), indicating that an alternative separation strategy will be required.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a very recent publication, the rapid differentiation of cannabinoid isobar sets (including THC/CBD) was demonstrated using ion mobility for (high concentration) cannabis products. 29 Coupled with reactive PS-MS, this could provide a route to further improving direct mass spectrometry THC measurements in biofluids. Routine cannabinoid drug testing of biofluids in a clinical setting requires reliable, high-throughput analytical strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Coupling the use of ion mobility strategies may also allow for the direct resolution of cannabinoid isobars. 29 While the derivatization employed in this reactive PS-MS method does not produce differentiable MS/MS spectra for THC and CBD (Fig. S2 †) and interference is observed, other derivatization agents may also have the potential to solve this issue.…”
Section: Future Workmentioning
confidence: 99%